The integration of psychology and medicine: an empirical study of curriculum reform from the perspective of China - Ma, Xinyan; Wang, Yuze; Pu, Yanmin; Shang, Herui; Zhang, Huiqun; Zhang, Xueqin (Frontiers in Psychology, 2024)
Under the background of new medicine, innovative reform of medical education is mushrooming in Mainland, China. New medicine advocates an innovative training mode supported by medicine + X discipline. In the present study, we made use of the advantages of medical colleges to reform the curriculum of applied psychology and constructed an innovative curriculum system by integrating medicine with psychology. This study aimed to evaluate the effects of the innovative curriculum system on the curriculum satisfaction of applied psychology and investigate the key factors that impact students’ curriculum satisfaction. The class of 2018–2022 college students from the Department of Applied Psychology who were under different course training systems were selected to complete the curriculum evaluation questionnaire to evaluate students’ curriculum satisfaction. The results demonstrated that curriculum satisfaction of the innovative curriculum system was significantly higher than that the one prior to the curriculum reform (P < 0.001), curriculum design, and teaching effect are the significant predictors affecting curriculum satisfaction. The results of this research provide innovative ideas for curriculum reform in psychology and strategies for the integration and development of medicine and psychology.